DETERMINAN KOEFISIEN RESPON LABA - Gunawan Santoso (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
This study aims to prove the effect of capital structure, the firm's reputation, growth opportunities, profitability, company size, systematic risk, earnings persistence, and the volatility of the earnings response coefficients with moderating variables unexpected earnings. This study uses the registered manufacturing sector in BEI period 2013--2015 with purposive sampling method. The amount of data used as many as 141 data consisting of 47 companies over three years. The analysis technique used in this research is multiple linear regression and moderating regression analysis This study proves that the unexpected earnings as a moderating variable still cannot strengthen the influence of the independent variable on the dependent variable. The results of hypothesis testing found that the volatility of the stock variable positive effect on earnings response coefficients. Acceptance of this hypothesis indicates that the market tended to respond to the publication of earnings on the company its stock price to fluctuate around the date of publication of earnings. While variable capital structure, the firm's reputation, growth opportunities, profitability, company size, systematic risk, and the persistence of earnings does not affect the earnings response